2015
DOI: 10.1088/0957-4484/26/6/065502
|View full text |Cite
|
Sign up to set email alerts
|

DNA motion induced by electrokinetic flow near an Au coated nanopore surface as voltage controlled gate

Abstract: The diffusion and drift motion of λ DNA molecules on Au coated membrane surface near nanopores prior to their translocation through solid-state nanopores are investigated using fluorescence microscopy. With the capability of controlling electric potential at the Au surface as a gate voltage, Vgate, the motions of DNA molecules vary dramatically near the nanopores in our observations, presumably generated by electrokinetic flow. We carefully investigate theses DNA motions with different values of Vgate in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…We observed and analyzed DNA dynamics near a nanopore and its direct translocation by fluorescence microscopy [7,29,30]. Through direct observation, we estimated the electric potential profile near a SiN nanopore [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed and analyzed DNA dynamics near a nanopore and its direct translocation by fluorescence microscopy [7,29,30]. Through direct observation, we estimated the electric potential profile near a SiN nanopore [7].…”
Section: Introductionmentioning
confidence: 99%
“…Through direct observation, we estimated the electric potential profile near a SiN nanopore [7]. By applying a gate voltage to an Au film on a SiN nanopore membrane, anomalous DNA motions induced by electroosmotic flow via a pore were observed [29]. By using a field-effect transistor nanopore, we developed a method for slowing the translocation speed of DNA by applying pulse voltages only on the field-effect transistor gate electrode, while both ionic solutions in the trans and cis reservoirs were kept at V = 0 [30].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that this on/off behavior is reproducible with multiple cycles. Previous simulation studies by Sugimoto et al 52 suggested that the use of voltage gating to control DNA translocation is mainly influenced by (i) electrophoretic force under an applied V pore , (ii) electroosmotic flow, and (iii) electrostatic interactions between DNA and the nanopore surface. In this case, molecular transport across the nanopore is switched off when the gold electrode possesses a net negative charge ( V gate < −100 mV).…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Not only that, in biomolecular detection, the potency of metallic nanopores includes an externally controllable electric potential owing to their ability to change flow direction by reversing the polarity of the potential difference between the pore and buffer solution. 21 Among expensive and complex nanostructuring and downscaling techniques including conventional lithography, electroplating, H3171 electron beam lithography (EBL) and the like, nanosphere lithography (NSL) has emanated as a simple and cheap colloid based lithography, particularly for the generation of highly periodic 2D metallic nanoparticles array on a large surface with 200-1000 nm range. 22,23 In this study, NSL was elaborated as the underlying process in Au nanoporous EGFET fabrication.…”
mentioning
confidence: 99%